Slow and Fast Evolving Endosymbiont Lineages: Positive Correlation between the Rates of Synonymous and Non-Synonymous Substitution - Silva, Francisco J. (Front Microbiol, 2015)
The availability of complete genome sequences of bacterial endosymbionts with strict vertical transmission to the host progeny opens the possibility to estimate molecular evolutionary rates in different lineages and understand the main biological mechanisms influencing these rates. We have compared the rates of evolution for non-synonymous and synonymous substitutions in nine bacterial endosymbiont lineages, belonging to four clades (Baumannia, Blochmannia, Portiera, and Sulcia). The main results are the observation of a positive correlation between both rates with differences among lineages of up to three orders of magnitude and that the substitution rates decrease over long endosymbioses. To explain these results we propose three mechanisms. The first, variations in the efficiencies of DNA replication and DNA repair systems, is unable to explain most of the observed differences. The second, variations in the generation time among bacterial lineages, would be based on the accumulation of fewer DNA replication errors per unit time in organisms with longer generation times. The third, a potential control of the endosymbiont DNA replication and repair systems through the transfer of nuclear-encoded proteins, could explain the lower rates in long-term obligate endosymbionts. Because the preservation of the genomic integrity of the harbored obligate endosymbiont would be advantageous for the insect host, biological mechanisms producing a general reduction in the rates of nucleotide substitution per unit of time would be a target for natural selection.